Analisis Kredibilitas Influencer dalam Meningkatkan Brand Awareness @Zaskiasungkarjakarta Melalui Konten Media Sosial Instagram - Alma Aninditha Zalianty; Daniel Handoko (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2026)
The rapid development of social media has made fashion brands, especially modest fashion, increasingly collaborate with influencers to increase brand awareness. This study discusses the role of influencer credibility in increasing brand awareness of the brand @zaskiasungkarjakarta through Instagram content. The method used a case study with a qualitative approach. Data was collected through interviews and documentation, then analyzed through the stages of data reduction, presentation, and drawing conclusions. The results show that influencer credibility plays a significant role in maintaining brand awareness. There are three main dimensions that are visible: expertise, trustworthiness, and attractiveness. Trustworthiness is evident from the honesty and consistency of influencers when showing or reviewing products. Meanwhile, attractiveness arises from the match between the influencer's lifestyle and image with the brand, making the audience feel more relatable and trusting. Overall, influencer credibility helps increase brand awareness from the brand recognition stage (people start to recognize), brand recall (people can remember again), until the brand finally becomes top of mind in the minds of the audience.